FORMULATION, OPTIMISATION AND EVALUATION OF MICROPARTICLES OF CURCUMIN-ZN COMPLEX - RAVINDRA B. LAWARE; DR. BHANUDAS S.KUCHEKAR (International Journal of Pharma and Bio Sciences, 2015)
In present study an attempt was made to prepare microparticulate drug delivery system of curcumin-Zn complex and evaluate it in albino rats spectroflurometrically. It was observed that curcumin-Zn complex was more soluble and stable than curcumin. Curcumin-Zn complex was prepared and encapsulated using sodium alginate. Characterization of prepared microparticles was done using FTIR, UV, SEM and DSC study. Microparticles thus obtained are further coated with various enteric polymers like eudragit S 100, eudragit L100, and cellulose acetate pthalate and ethyl cellulose at different coating thickness to control the release. Microparticles were evaluated for encapsulation efficiency, drug loading and in vitro drug release. Microparticles coated with cellulose acetate pthalate showed most satisfactory and controlled release with 502 min time for 60% cumulative release. Curcumin-Zn was estimated in serum after oral administration of microparticles to rats by using spectroflurometry. Estimation of curcumin in serum by spectroflurometry showed that drug concentration is maintained in the blood for longer time with tmax of 6 hours.